A Computational Study of Complexes Relevant to the Mechanism of the Friedel-Crafts Reaction - Lanska, John R. (My University, 2015)
The purpose of this study was to find out the structural and bonding properties of the intermediates in the Friedel-Crafts reactions.
Color poster with text and images.
Keywords: RX-MX complexes; Friedel-Crafts reactions; Chemistry; Posters